Interconnection Between Human and Environmental Degradation In Tere Liye's Novel Hujan: A Literary Ecocriticism - Adiwinata, Akbar; Anugrah, Inayah (Journal of Language, Literature and Teaching, 2025)
This paper examines the interconnection between human and environmental degradation in Tere Liye's novel Hujan using the ecocritical approach proposed by Gerg Garrard. The focus of this study is how human actions affect the environment and how nature responds to these actions. This research uses a qualitative descriptive method, where data is taken from novel texts and analyzed using ecocritical theory. The results of the analysis show that this novel describes various forms of pollution, habitat destruction, and the disastrous impacts caused by human exploitation. Pollution due to the use of environmentally unsustainable energy sources and policies that harm nature are the main themes. In addition, the image of wilderness as a source of balance for ecosystems and other living things is reduced because of the destruction. Ecological disasters that occur, whether natural or made by human, create conflicts between human needs and natural resource capacity. With an emphasis on the interrelationship between humans and the environment, this study aims to raise awareness about the importance of preserving the environment through a literary lens.